Derivation of nickel-cobalt-iron hydroxide doped with scandium from laterite nickel ore, its preparation method and application

CN117867557BActive Publication Date: 2026-10-30BEIJING UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410125930.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-30
Publication Date
2026-10-30
Estimated Expiration
2044-01-30

AI Technical Summary

Technical Problem

[0005]本发明所要解决的技术问题是现有技术中鲜有对红土镍矿中钪的成熟高效富集与回收技术研究报道,钪无法得到有效回收,造成钪资源的浪费,且传统红土镍矿资源利用的净化过程复杂等技术问题

Benefits of technology

[0016]有益效果:本发明提出了一种钪掺杂镍铁钴氢氧化物制备2,5-呋喃二甲酸的方法,先将红土镍矿置于去离子水中形成溶液A,加入浓硫酸调节pH并搅拌进行酸浸反应,固液分离后得到溶液B,使得红土镍矿中的铁、镍、钴和钪等转化成离子态进入到溶液B中,红土镍矿中的钙等杂质形成硫酸钙等沉淀分离出来;向溶液B中加入尿素,搅拌后得到混合溶液,以通过尿素中和溶液B中过量的H+,并创造碱性条件以在泡沫镍上原位生长氢氧化物;将泡沫镍材料进行预处理后得到的泡沫镍初始材料置于混合溶液中,然后放入聚四氟乙烯高压反应釜中并置于烘箱中进行反应,冷却得到复合材料,通过将泡沫镍初始材料作为多孔电催化剂载体,通过水热法合成钪掺杂镍铁钴氢氧化物;将5-羟甲基糠醛溶于碱性溶液中得到溶液C,向H型电解池中放入溶液C、参比电极、对电极和钪掺杂镍铁钴氢氧化物,然后将溶液C进行电催化转化后,得到2,5-呋喃二甲酸,通过将制备的钪掺杂镍铁钴氢氧化物作为电催化剂用作工作电极,使用三电极体系,由施加到阳极的电位驱动,在温和条件下实现电催化氧化5-羟甲基糠醛定向转化为可再生、环境友好、应用前景广泛的2,5-呋喃二甲酸,具有绿色、无污染、成本低等优势。本发明以红土镍矿为原料,通过调控浸出流程,将红土镍矿通过简单、快速的技术手段直接转化为过渡金属催化剂钪掺杂镍钴铁氢氧化物,该催化剂具有优异的电催化性能,且制备过程中避免了传统矿物相一系列复杂的提取和分离过程,制备出的催化剂可用于电催化实际应用中,有效地降低了成本。同时,电催化氧化反应过程条件温和,绿色无污染,操作简单,产物的选择性较好,法拉第效率较高,为红土镍矿的环境友好资源化处理提供了新的策略和思路。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117867557B_ABST
    Figure CN117867557B_ABST
Patent Text Reader

Abstract

The application provides a laterite nickel ore derived scandium-doped nickel-cobalt-iron hydroxide, a preparation method and application thereof, and the application comprises a method for preparing 2,5-furan dicarboxylic acid, which comprises the following steps: placing laterite nickel ore in deionized water, adding concentrated sulfuric acid to adjust pH, and obtaining a solution B; placing a foamed nickel initial material in the solution B, putting the foamed nickel initial material into a polytetrafluoroethylene high-pressure reaction kettle, and placing the foamed nickel initial material in an oven to perform reaction, and obtaining a composite material after cooling; cleaning the composite material with deionized water and ethanol, and drying to obtain scandium-doped nickel-iron-cobalt hydroxide; putting an alkaline solution containing 5-hydroxymethylfurfural, a reference electrode, a counter electrode and the scandium-doped nickel-iron-cobalt hydroxide into an H-type electrolytic cell, and obtaining 2,5-furan dicarboxylic acid after electrolysis. The application directly converts nickel, iron, cobalt and scandium in the laterite nickel ore into the scandium-doped nickel-cobalt-iron hydroxide, and uses the scandium-doped nickel-cobalt-iron hydroxide to prepare 2,5-furan dicarboxylic acid, so that comprehensive and efficient recycling of scandium and other metals in the laterite nickel ore is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of comprehensive utilization technology of laterite nickel ore, and specifically relates to scandium-doped nickel cobalt iron hydroxide derived from laterite nickel ore, its preparation method and application. Background Technology

[0002] my country faces a relative scarcity of nickel, cobalt, and scandium resources, with an import dependency rate as high as 80%. The efficient development of overseas laterite nickel ore resources is a key national strategy. However, existing hydrometallurgical processes for laterite nickel ore suffer from problems such as long process flows, low nickel-cobalt yields, high acid / energy consumption, ineffective recovery of associated rare earth elements, large waste emissions, direct discharge of iron-containing tailings causing serious resource waste and environmental pollution, significant impact of process scaling on production efficiency, and stringent operating conditions for high-pressure acid leaching equipment. Therefore, in-depth research is urgently needed on key technologies for the efficient and clean extraction and comprehensive utilization of laterite nickel ore resources to provide scientific support for ensuring the security of these strategic metals.

[0003] Scandium is found in lateritic nickel ore at low grades and dispersed (30–40 ppm). The concentration of scandium in high-pressure acid leaching solutions is only 5–15 mg / L. Iron, aluminum, silicon, calcium, magnesium, manganese, nickel, and cobalt all interfere with scandium separation and extraction, and their content and concentration are hundreds to tens of thousands of times higher than scandium. This makes it impossible to effectively recover scandium from lateritic nickel ore during the smelting process; most of it ends up in the nickel-cobalt hydroxide intermediate product, wasting scandium resources and reducing product quality. Currently, there are few reports on mature and efficient enrichment and recovery technologies for scandium in lateritic nickel ore.

[0004] Therefore, how to directly convert nickel, iron, cobalt, and scandium in laterite nickel ore into scandium-doped nickel-cobalt-iron hydroxide and use it as an electrocatalyst to prepare renewable biomass resource 2,5-furandicarboxylic acid (FDCA), thereby achieving efficient recovery and utilization of scandium and effectively avoiding the complex purification process of traditional laterite nickel ore resource utilization, is a problem that urgently needs to be solved by those skilled in the art. Summary of the Invention

[0005] The technical problem to be solved by this invention is that there are few research reports on mature and efficient enrichment and recovery technologies for scandium in laterite nickel ore in the existing technology, scandium cannot be effectively recovered, resulting in the waste of scandium resources, and the purification process of traditional laterite nickel ore resource utilization is complicated.

[0006] To address the aforementioned problems, a first aspect of the present invention provides a method for preparing 2,5-furandicarboxylic acid from scandium-doped nickel-iron-cobalt hydroxide. The method comprises: pretreating nickel foam material to obtain initial nickel foam material; placing laterite nickel ore in deionized water to form solution A; adding concentrated sulfuric acid to solution A to adjust the pH and stirring to carry out the reaction; performing solid-liquid separation after the reaction is complete to obtain solution B; adding urea to solution B and stirring to obtain a mixed solution; placing the initial nickel foam material in the mixed solution; and then placing the mixed solution into a polytetrafluoroethylene high-pressure reactor. After the reaction, the polytetrafluoroethylene high-pressure reactor is placed in an oven for reaction. After the reaction is completed, the polytetrafluoroethylene high-pressure reactor is removed and cooled to room temperature to obtain a composite material. The composite material is washed with deionized water and ethanol, and then dried in a vacuum dry oven to obtain scandium-doped nickel-iron-cobalt hydroxide. 5-hydroxymethylfurfural is dissolved in an alkaline solution to obtain solution C. Solution C, a reference electrode, a counter electrode, and the scandium-doped nickel-iron-cobalt hydroxide are placed in an H-type electrolytic cell. Then, solution C is subjected to electrocatalytic conversion to obtain 2,5-furandicarboxylic acid.

[0007] In the first aspect, the pretreatment of the nickel foam material to obtain the initial nickel foam material includes: cutting the nickel foam material with a thickness of 0.5 mm into nickel foam sheets with a size of 1 cm × 1 cm × 0.5 mm, and subjecting the nickel foam sheets to ultrasonic treatment with hydrochloric acid for 15 min, ultrasonic treatment with acetone for 15 min, ultrasonic treatment with ethanol for 15 min, and ultrasonic treatment with ultrapure water for 15 min in sequence to obtain the initial nickel foam material, wherein the concentration of the hydrochloric acid is 3 mol / L.

[0008] In the first aspect, the step of placing lateritic nickel ore in deionized water to form solution A, adding concentrated sulfuric acid to solution A to adjust the pH and stirring to carry out the reaction: the mass of the lateritic nickel ore is 200mg to 600mg, the volume of the deionized water is 30mL to 80mL, the pH value is 1.2 to 3.5, and the stirring time is 5h to 12h; the step of placing the polytetrafluoroethylene high-pressure reactor in an oven to carry out the reaction, the reaction temperature is 120℃ to 200℃, the reaction time is 6h to 24h, and the capacity of the polytetrafluoroethylene high-pressure reactor is 100mL; the step of placing the cleaned composite material in a vacuum drying oven to dry, the drying temperature is 60℃, and the drying time is 12h.

[0009] In the first aspect, the step of adding urea to solution B and stirring to obtain a mixed solution includes: detecting the pH value of solution B; adding a first molar mass of urea to solution B according to the pH value and the urea hydrolysis equation to adjust the pH of solution B to neutral; continuing to add a second molar mass of urea to the neutral solution B and stirring for 10 min to 60 min to obtain the mixed solution, wherein the ratio of the second molar mass to the molar mass of nickel metal in the laterite nickel ore is 2:1 to 5:1.

[0010] In the first aspect, the concentration of 5-hydroxymethylfurfural is 10 mmol / L to 100 mmol / L, the alkaline solution is a 1 mol / L to 3 mol / L KOH solution, the reference electrode is Hg / HgO, the counter electrode is a carbon rod, and the electrocatalytic conversion potential is 1.4 V to 1.6 V (vs. RHE).

[0011] Secondly, the present invention provides a method for preparing scandium-doped nickel-cobalt-iron hydroxide derived from laterite nickel ore. The preparation method includes: pretreating nickel foam material to obtain initial nickel foam material; placing laterite nickel ore in deionized water to form solution A; adding concentrated sulfuric acid to solution A to adjust the pH and stirring to carry out the reaction; performing solid-liquid separation after the reaction is completed to obtain solution B; adding urea to solution B and stirring to obtain a mixed solution; placing the initial nickel foam material in the mixed solution; then placing the mixed solution in a polytetrafluoroethylene (PTFE) high-pressure reactor; placing the PTFE high-pressure reactor in an oven to carry out the reaction; after the reaction is completed, removing the PTFE high-pressure reactor and cooling it to room temperature to obtain a composite material; washing the composite material with deionized water and ethanol; and drying the washed composite material in a vacuum dry oven to obtain scandium-doped nickel-cobalt-iron hydroxide.

[0012] In the second aspect, the pretreatment of the nickel foam material to obtain the initial nickel foam material includes: cutting the nickel foam material with a thickness of 0.5 mm into nickel foam sheets with a size of 1 cm × 1 cm × 0.5 mm, and subjecting the nickel foam sheets to ultrasonic treatment with hydrochloric acid for 15 min, ultrasonic treatment with acetone for 15 min, ultrasonic treatment with ethanol for 15 min, and ultrasonic treatment with ultrapure water for 15 min in sequence to obtain the initial nickel foam material, wherein the concentration of the hydrochloric acid is 3 mol / L.

[0013] In the second aspect, the step of placing lateritic nickel ore in deionized water to form solution A, adding concentrated sulfuric acid to solution A to adjust the pH and stirring to carry out the reaction: the mass of the lateritic nickel ore is 200mg to 600mg, the volume of the deionized water is 30mL to 80mL, the pH value is 1.2 to 3.5, and the stirring time is 5h to 12h; the step of placing the polytetrafluoroethylene high-pressure reactor in an oven to carry out the reaction at a reaction temperature of 120℃ to 200℃ for a reaction time of 6h to 24h, and the capacity of the polytetrafluoroethylene high-pressure reactor is 100mL; and the step of placing the cleaned composite material in a vacuum drying oven to dry at a drying temperature of 60℃ for a drying time of 12h.

[0014] In the second aspect, the step of adding urea to solution B and stirring to obtain a mixed solution includes: detecting the pH value of solution B; adding a first molar mass of urea to solution B according to the pH value and the urea hydrolysis equation to adjust the pH of solution B to neutral; continuing to add a second molar mass of urea to the neutral solution B and stirring for 10 min to 60 min to obtain the mixed solution, wherein the ratio of the second molar mass to the molar mass of nickel metal in the laterite nickel ore is 2:1 to 5:1.

[0015] Thirdly, the present invention provides a lateritic nickel ore-derived scandium-doped nickel cobalt iron hydroxide, characterized in that it is prepared by the aforementioned preparation method, and the scandium-doped nickel cobalt iron hydroxide has the following uses: as an electrocatalyst for the preparation of 2,5-furandicarboxylic acid.

[0016] Beneficial Effects: This invention proposes a method for preparing 2,5-furandicarboxylic acid from scandium-doped nickel-iron-cobalt hydroxide. First, lateritic nickel ore is placed in deionized water to form solution A. Concentrated sulfuric acid is added to adjust the pH, and the mixture is stirred to carry out an acid leaching reaction. After solid-liquid separation, solution B is obtained, allowing iron, nickel, cobalt, and scandium in the lateritic nickel ore to be converted into ions and enter solution B. Impurities such as calcium in the lateritic nickel ore are separated as calcium sulfate precipitates. Urea is added to solution B, and after stirring, a mixed solution is obtained. This solution neutralizes excess H+ in solution B through the addition of urea. +Alkaline conditions were created to grow hydroxides in situ on nickel foam. Initial nickel foam material, obtained after pretreatment, was placed in a mixed solution, then placed in a polytetrafluoroethylene high-pressure reactor and placed in an oven for reaction. After cooling, a composite material was obtained. Scandium-doped nickel-iron-cobalt hydroxide was synthesized via a hydrothermal method using the initial nickel foam material as a porous electrocatalyst support. 5-Hydroxymethylfurfural was dissolved in an alkaline solution to obtain solution C. Solution C, a reference electrode, a counter electrode, and scandium-doped nickel-iron-cobalt hydroxide were placed in an H-type electrolytic cell. Solution C was then electrocatalytically converted to 2,5-furandicarboxylic acid. Using the prepared scandium-doped nickel-iron-cobalt hydroxide as an electrocatalyst and a three-electrode system driven by the potential applied to the anode, the electrocatalytic oxidation of 5-hydroxymethylfurfural was directionally converted into renewable, environmentally friendly, and widely applicable 2,5-furandicarboxylic acid under mild conditions. This method offers advantages such as being green, pollution-free, and low-cost. This invention uses lateritic nickel ore as raw material and, through controlled leaching, directly converts it into scandium-doped nickel-cobalt-iron hydroxide using a simple and rapid technique. This catalyst exhibits excellent electrocatalytic performance, and its preparation avoids the complex extraction and separation processes inherent in traditional mineral phases. The resulting catalyst can be used in practical electrocatalytic applications, effectively reducing costs. Furthermore, the electrocatalytic oxidation reaction is conducted under mild, environmentally friendly, and pollution-free conditions, is simple to operate, exhibits good product selectivity, and demonstrates high Faraday efficiency, providing a new strategy and approach for the environmentally friendly resource utilization of lateritic nickel ore. Attached Figure Description

[0017] To more clearly illustrate the technical solutions in the embodiments of this specification or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0018] Figure 1 This is a flowchart of the method for preparing 2,5-furandicarboxylic acid using laterite nickel ore in an embodiment of the present invention;

[0019] Figure 2 This is a SEM image of scandium-doped nickel-iron-cobalt hydroxide in Example 5 of the present invention;

[0020] Figure 3 The XRD pattern of scandium-doped nickel-iron-cobalt hydroxide in Example 5 of this invention;

[0021] Figure 4 The linear sweep voltammetric curves of scandium-doped nickel-iron-cobalt hydroxide in 1 mol / L KOH and in solution C are shown in Example 5 of this invention. Detailed Implementation

[0022] The technical solutions of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention are within the scope of protection of the present invention.

[0023] Furthermore, throughout this specification, unless otherwise specified, the terminology used herein should be understood as having the meaning commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. In the event of any conflict, this specification shall prevail.

[0024] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.

[0025] Example 1

[0026] like Figure 1 As shown, this embodiment provides a method for preparing 2,5-furandicarboxylic acid from scandium-doped nickel-iron-cobalt hydroxide. The method includes: S101 pretreating nickel foam material to obtain initial nickel foam material; S102 placing laterite nickel ore in deionized water to form solution A, adding concentrated sulfuric acid to solution A to adjust the pH and stirring to carry out the reaction, and performing solid-liquid separation after the reaction is completed to obtain solution B; S103 adding urea to solution B, stirring to obtain a mixed solution, placing the initial nickel foam material in the mixed solution, and then placing the mixed solution into a polytetrafluoroethylene high-pressure reactor. The polytetrafluoroethylene (PTFE) high-pressure reactor was placed in an oven for reaction. After the reaction, the PTFE high-pressure reactor was removed and cooled to room temperature to obtain a composite material. In step S104, the composite material was washed with deionized water and ethanol, and then dried in a vacuum oven to obtain scandium-doped nickel-iron-cobalt hydroxide grown on nickel foam. In step S105, 5-hydroxymethylfurfural was dissolved in an alkaline solution to obtain solution C. Solution C, a reference electrode, a counter electrode, and the scandium-doped nickel-iron-cobalt hydroxide were added to an H-type electrolytic cell. Solution C was then subjected to electrocatalytic conversion to obtain 2,5-furandicarboxylic acid. Solution C served as the anolyte in the H-type electrolytic cell, while the cathode electrolyte was an alkaline solution without added 5-hydroxymethylfurfural.

[0027] Specifically, this invention proposes a method for preparing 2,5-furandicarboxylic acid from scandium-doped nickel-iron-cobalt hydroxide. First, lateritic nickel ore is placed in deionized water to form solution A. Concentrated sulfuric acid is added to adjust the pH, and the mixture is stirred to carry out an acid leaching reaction. After solid-liquid separation, solution B is obtained, allowing iron, nickel, cobalt, and scandium in the lateritic nickel ore to be converted into ions and enter solution B. Impurities such as calcium in the lateritic nickel ore are separated as calcium sulfate precipitates. Urea is added to solution B, and after stirring, a mixed solution is obtained. This solution neutralizes excess H+ in solution B through the urea. + Alkaline conditions were created to grow hydroxides in situ on nickel foam. Initial nickel foam material, obtained after pretreatment, was placed in a mixed solution, then placed in a polytetrafluoroethylene high-pressure reactor and placed in an oven for reaction. After cooling, a composite material was obtained. Scandium-doped nickel-iron-cobalt hydroxide was synthesized via a hydrothermal method using the initial nickel foam material as a porous electrocatalyst support. 5-Hydroxymethylfurfural was dissolved in an alkaline solution to obtain solution C. Solution C, a reference electrode, a counter electrode, and scandium-doped nickel-iron-cobalt hydroxide were placed in an H-type electrolytic cell. Solution C was then electrocatalytically converted to 2,5-furandicarboxylic acid. Using the prepared scandium-doped nickel-iron-cobalt hydroxide as an electrocatalyst and a three-electrode system driven by the potential applied to the anode, the electrocatalytic oxidation of 5-hydroxymethylfurfural was directionally converted into renewable, environmentally friendly, and widely applicable 2,5-furandicarboxylic acid under mild conditions. This method offers advantages such as being green, pollution-free, and low-cost. Compared to existing research and technologies that involve separating and purifying metal elements from laterite nickel ore, and then using the obtained metal elements to synthesize electrocatalysts for electrocatalytic conversion, this invention uses laterite nickel ore as raw material. By controlling the leaching process, it directly converts laterite nickel ore into a scandium-doped nickel-cobalt-iron hydroxide catalyst using a simple and rapid technique. This catalyst exhibits excellent electrocatalytic performance, and its preparation avoids a series of complex extraction and separation processes typical of traditional mineral phases. The prepared catalyst can be used in practical electrocatalytic applications, effectively reducing costs. Furthermore, the electrocatalytic oxidation reaction process is mild, environmentally friendly, and pollution-free, with simple operation, good product selectivity, and high Faraday efficiency, providing a new strategy and approach for the environmentally friendly resource utilization of laterite nickel ore.

[0028] In some possible implementations, the pretreatment of the nickel foam material to obtain the initial nickel foam material includes: cutting the nickel foam material with a thickness of 0.5 mm into a nickel foam sheet with a size of 1 cm × 1 cm × 0.5 mm, and subjecting the nickel foam sheet to ultrasonic treatment with hydrochloric acid for 15 min, ultrasonic treatment with acetone for 15 min, ultrasonic treatment with ethanol for 15 min, and ultrasonic treatment with ultrapure water for 15 min in sequence to obtain the initial nickel foam material, wherein the concentration of the hydrochloric acid is 3 mol / L.

[0029] Those skilled in the art will understand that sequentially subjecting a 1cm×1cm×0.5mm nickel foam sheet to ultrasonic treatment with hydrochloric acid for 15 minutes, acetone for 15 minutes, ethanol for 15 minutes, and ultrapure water for 15 minutes, with the hydrochloric acid concentration being 3mol / L, is beneficial for removing the oxide film on the surface of the nickel foam sheet through ultrasonic treatment with hydrochloric acid, removing oil stains through ultrasonic treatment with acetone, and finally undergoing ultrasonic treatment with ethanol and ultrapure water in sequence to obtain pure initial material of nickel foam, which is conducive to the subsequent in-situ growth of scandium-doped nickel-iron-cobalt hydroxide on the nickel foam.

[0030] In some possible embodiments, the step of placing lateritic nickel ore in deionized water to form solution A, adding concentrated sulfuric acid to solution A to adjust the pH and stirring to carry out the reaction: the mass of the lateritic nickel ore is 200mg to 600mg, the volume of the deionized water is 30mL to 80mL, the pH value is 1.2 to 3.5, and the stirring time is 5h to 12h; the step of placing the polytetrafluoroethylene high-pressure reactor in an oven to carry out the reaction at a reaction temperature of 120℃ to 200℃ for a reaction time of 6h to 24h, and the capacity of the polytetrafluoroethylene high-pressure reactor is 100mL; and the step of placing the cleaned composite material in a vacuum drying oven to dry at a drying temperature of 60℃ for 12h.

[0031] This is because the mass of laterite nickel ore is 200mg to 600mg, the volume of deionized water is 30mL to 80mL, the pH value is 1.2 to 3.5, and the stirring time is 5h to 12h. Under acidic conditions, iron, nickel, cobalt, and scandium in the laterite nickel ore are converted into ionic states and enter the solution. Impurities such as calcium in the laterite nickel ore form calcium sulfate and other substances that precipitate and separate out. The reaction is complete, and the simultaneous extraction of iron, nickel, cobalt, and scandium elements from the laterite nickel ore is achieved.

[0032] In some possible implementations, the step of adding urea to solution B and stirring to obtain a mixed solution includes: detecting the pH value of solution B; adding a first molar mass of urea to solution B according to the pH value and the urea hydrolysis equation to adjust the pH of solution B to neutral; and continuing to add a second molar mass of urea to the neutral solution B and stirring for 10 min to 60 min to obtain the mixed solution, wherein the ratio of the second molar mass to the molar mass of nickel metal in the laterite nickel ore is 2:1 to 5:1. Specifically, adding a first molar mass of urea to solution B according to the pH value and the urea hydrolysis equation to adjust the pH of solution B to neutral can be achieved by obtaining the hydrogen ion concentration c(H+) from the pH value of solution B. + ), and based on the ion product constant K of water. w =c(H + )×c(OH -), to obtain the concentration c(OH) of the hydroxide ions to be added. - Then, based on the urea hydrolysis equation, as shown in the following formula, calculate the first molar mass of urea;

[0033] (NH2)2CO+3H2O→2NH3·H2O+CO2;

[0034] NH3·H2O→NH4 + +OH - .

[0035] This is because, after adjusting the pH of solution A with concentrated sulfuric acid, the resulting solution B contains H+. + If the amount is too large, first add the first mole of urea to neutralize the excess H in solution B. + To neutralize, a second molar mass of urea is added, which is 2-5 times the molar mass of nickel metal in the laterite nickel ore to be reacted, so that the iron, nickel, cobalt and scandium in the laterite nickel ore can fully react under alkaline conditions to grow in situ on the nickel foam as an ultrathin nanosheet structure of scandium-doped nickel cobalt iron hydroxide.

[0036] In some possible embodiments, the concentration of 5-hydroxymethylfurfural is 10 mmol / L to 100 mmol / L, the alkaline solution is 1 mol / L to 3 mol / L KOH solution, the reference electrode is Hg / HgO, the counter electrode is a carbon rod, and the electrocatalytic conversion potential is 1.4 V to 1.6 V (vs. RHE).

[0037] Example 2

[0038] This second embodiment provides a method for preparing scandium-doped nickel-cobalt-iron hydroxide derived from laterite nickel ore. The preparation method includes: pretreating nickel foam material to obtain initial nickel foam material; placing laterite nickel ore in deionized water to form solution A; adding concentrated sulfuric acid to solution A to adjust the pH and stirring to carry out the reaction; after the reaction is completed, performing solid-liquid separation to obtain solution B; adding urea to solution B and stirring to obtain a mixed solution; placing the initial nickel foam material in the mixed solution; then placing the mixed solution in a polytetrafluoroethylene (PTFE) high-pressure reactor; placing the PTFE high-pressure reactor in an oven to carry out the reaction; after the reaction is completed, removing the PTFE high-pressure reactor and cooling it to room temperature to obtain a composite material; washing the composite material with deionized water and ethanol; and drying the washed composite material in a vacuum dry oven to obtain scandium-doped nickel-cobalt-iron hydroxide.

[0039] In some possible implementations, the pretreatment of the nickel foam material to obtain the initial nickel foam material includes: cutting the nickel foam material with a thickness of 0.5 mm into a nickel foam sheet with a size of 1 cm × 1 cm × 0.5 mm, and subjecting the nickel foam sheet to ultrasonic treatment with hydrochloric acid for 15 min, ultrasonic treatment with acetone for 15 min, ultrasonic treatment with ethanol for 15 min, and ultrasonic treatment with ultrapure water for 15 min in sequence to obtain the initial nickel foam material, wherein the concentration of the hydrochloric acid is 3 mol / L.

[0040] In some possible embodiments, the step of placing lateritic nickel ore in deionized water to form solution A, adding concentrated sulfuric acid to solution A to adjust the pH and stirring to carry out the reaction: the mass of the lateritic nickel ore is 200mg to 600mg, the volume of the deionized water is 30mL to 80mL, the pH value is 1.2 to 3.5, and the stirring time is 5h to 12h; the step of placing the polytetrafluoroethylene high-pressure reactor in an oven to carry out the reaction at a reaction temperature of 120℃ to 200℃ for a reaction time of 6h to 24h, and the capacity of the polytetrafluoroethylene high-pressure reactor is 100mL; and the step of placing the cleaned composite material in a vacuum drying oven to dry at a drying temperature of 60℃ for 12h.

[0041] In some possible implementations, the step of adding urea to solution B and stirring to obtain a mixed solution includes: detecting the pH value of solution B; adding a first molar mass of urea to solution B according to the pH value and the urea hydrolysis equation to adjust the pH of solution B to neutral; continuing to add a second molar mass of urea to the neutral solution B and stirring for 10 min to 60 min to obtain the mixed solution, wherein the ratio of the second molar mass to the molar mass of nickel metal in the laterite nickel ore is 2:1 to 5:1.

[0042] In some possible implementations, the scandium-doped nickel-cobalt-iron hydroxide is used as an electrocatalyst for the preparation of 2,5-furandicarboxylic acid.

[0043] It should be noted that the preparation method of scandium-doped nickel cobalt iron hydroxide derived from laterite nickel ore provided in this embodiment 2 is the same as the scandium-doped nickel cobalt iron hydroxide described in this embodiment 1. The implementation principle and technical concept are exactly the same as those in embodiment 1. Therefore, for the parts not described in detail in this embodiment 2, please refer to embodiment 1. They will not be repeated here.

[0044] To further illustrate the technical solution of this application and support the technical problem to be solved by this application, specific examples of the method for preparing 2,5-furandicarboxylic acid using lateritic nickel ore are provided below, as in Examples 3-8. It should be noted that the raw material used in Examples 3-8 is the same type of lateritic nickel ore. The content of metal elements in the lateritic nickel ore was tested by XRF, and the specific test results are shown in Table 1.

[0045] Table 1

[0046] 38.6 12.5 13.0 5.0 21.3 9.6

[0047] Example 3

[0048] This embodiment prepares 2,5-furandicarboxylic acid from scandium-doped nickel-iron-cobalt hydroxide using the following steps:

[0049] Pretreatment of nickel foam material yields initial nickel foam material; the pretreatment of nickel foam material to obtain initial nickel foam material includes: cutting the nickel foam material with a thickness of 0.5 mm into a nickel foam sheet with a size of 1 cm × 1 cm × 0.5 mm, and subjecting the nickel foam sheet to ultrasonic treatment with hydrochloric acid for 15 min, ultrasonic treatment with acetone for 15 min, ultrasonic treatment with ethanol for 15 min, and ultrasonic treatment with ultrapure water for 15 min in sequence to obtain the initial nickel foam material, wherein the concentration of hydrochloric acid is 3 mol / L;

[0050] 200 mg of laterite nickel ore was placed in 30 mL of deionized water to form solution A. Concentrated sulfuric acid was added to solution A to adjust the pH to 3.5, and the mixture was stirred for 5 h to carry out the reaction. After the reaction was completed, solid-liquid separation was performed to obtain solution B.

[0051] Urea is added to solution B, and the mixture is stirred to obtain a mixed solution. The process of adding urea to solution B and stirring to obtain the mixed solution includes: detecting the pH value of solution B; adding a first molar mass of urea to solution B according to the pH value and the urea hydrolysis equation to adjust the pH of solution B to neutral; adding a second molar mass of urea to the neutral solution B and stirring for 10 minutes to obtain the mixed solution, wherein the ratio of the second molar mass to the molar mass of nickel metal in the laterite nickel ore is 2:1; placing the initial foamed nickel material in the mixed solution, then placing the mixed solution into a 100 mL polytetrafluoroethylene (PTFE) high-pressure reactor, placing the PTFE high-pressure reactor in an oven for reaction at 120°C for 6 hours; after the reaction, removing the PTFE high-pressure reactor and cooling it to room temperature to obtain the composite material.

[0052] The composite material was cleaned with deionized water and ethanol, and then dried in a vacuum drying oven at 60°C for 12 hours to obtain scandium-doped nickel-iron-cobalt hydroxide.

[0053] 5-Hydroxymethylfurfural was dissolved in an alkaline solution to obtain solution C. Solution C, a reference electrode, a counter electrode, and the scandium-doped nickel-iron-cobalt hydroxide were placed in an H-type electrolytic cell. Solution C was then subjected to electrocatalytic conversion to obtain 2,5-furandicarboxylic acid. The concentration of 5-hydroxymethylfurfural was 10 mmol / L, the alkaline solution was a 1 mol / L KOH solution, the reference electrode was Hg / HgO, the counter electrode was a carbon rod, and the electrocatalytic conversion potential was 1.4 V (vs. RHE). Solution C was used as the electrolyte in the anolyte of the H-type electrolytic cell, and the electrolyte in the cathode of the H-type electrolytic cell was a 1 mol / L KOH solution without added 5-hydroxymethylfurfural.

[0054] Example 4

[0055] This embodiment prepares 2,5-furandicarboxylic acid from scandium-doped nickel-iron-cobalt hydroxide using the following steps:

[0056] Pretreatment of nickel foam material yields initial nickel foam material; the pretreatment of nickel foam material to obtain initial nickel foam material includes: cutting the nickel foam material with a thickness of 0.5 mm into a nickel foam sheet with a size of 1 cm × 1 cm × 0.5 mm, and subjecting the nickel foam sheet to ultrasonic treatment with hydrochloric acid for 15 min, ultrasonic treatment with acetone for 15 min, ultrasonic treatment with ethanol for 15 min, and ultrasonic treatment with ultrapure water for 15 min in sequence to obtain the initial nickel foam material, wherein the concentration of hydrochloric acid is 3 mol / L;

[0057] 400 mg of laterite nickel ore was placed in 50 mL of deionized water to form solution A. Concentrated sulfuric acid was added to solution A to adjust the pH to 2, and the mixture was stirred for 7 h to carry out the reaction. After the reaction was completed, solid-liquid separation was performed to obtain solution B.

[0058] Urea is added to solution B, and the mixture is stirred to obtain a mixed solution. The process of adding urea to solution B and stirring to obtain the mixed solution includes: detecting the pH value of solution B; adding a first molar mass of urea to solution B according to the pH value and the urea hydrolysis equation to adjust the pH of solution B to neutral; continuing to add a second molar mass of urea to the neutral solution B and stirring for 20 minutes to obtain the mixed solution, wherein the ratio of the second molar mass to the molar mass of nickel metal in the laterite nickel ore is 3:1; placing the initial foamed nickel material in the mixed solution, then placing the mixed solution into a 100 mL polytetrafluoroethylene (PTFE) high-pressure reactor, placing the PTFE high-pressure reactor in an oven for reaction at a reaction temperature of 160°C for 12 hours; after the reaction is completed, removing the PTFE high-pressure reactor and cooling it to room temperature to obtain the composite material.

[0059] The composite material was cleaned with deionized water and ethanol, and then dried in a vacuum drying oven at 60°C for 12 hours to obtain scandium-doped nickel-iron-cobalt hydroxide.

[0060] 5-Hydroxymethylfurfural was dissolved in an alkaline solution to obtain solution C. Solution C, a reference electrode, a counter electrode, and the scandium-doped nickel-iron-cobalt hydroxide were placed in an H-type electrolytic cell. Solution C was then subjected to electrocatalytic conversion to obtain 2,5-furandicarboxylic acid. The concentration of 5-hydroxymethylfurfural was 10 mmol / L, the alkaline solution was a 1 mol / L KOH solution, the reference electrode was Hg / HgO, the counter electrode was a carbon rod, and the electrocatalytic conversion potential was 1.5 V (vs. RHE). Solution C was used as the electrolyte in the anolyte of the H-type electrolytic cell, and the electrolyte in the cathode of the H-type electrolytic cell was a 1 mol / L KOH solution without added 5-hydroxymethylfurfural.

[0061] Example 5

[0062] This embodiment prepares 2,5-furandicarboxylic acid from scandium-doped nickel-iron-cobalt hydroxide using the following steps:

[0063] Pretreatment of nickel foam material yields initial nickel foam material; the pretreatment of nickel foam material to obtain initial nickel foam material includes: cutting the nickel foam material with a thickness of 0.5 mm into a nickel foam sheet with a size of 1 cm × 1 cm × 0.5 mm, and subjecting the nickel foam sheet to ultrasonic treatment with hydrochloric acid for 15 min, ultrasonic treatment with acetone for 15 min, ultrasonic treatment with ethanol for 15 min, and ultrasonic treatment with ultrapure water for 15 min in sequence to obtain the initial nickel foam material, wherein the concentration of hydrochloric acid is 3 mol / L;

[0064] 600 mg of laterite nickel ore was placed in 80 mL of deionized water to form solution A. Concentrated sulfuric acid was added to solution A to adjust the pH to 1.2, and the mixture was stirred for 12 h to carry out the reaction. After the reaction was completed, solid-liquid separation was performed to obtain solution B.

[0065] Urea is added to solution B, and the mixture is stirred to obtain a mixed solution. The steps of adding urea to solution B and stirring to obtain the mixed solution include: detecting the pH value of solution B; adding a first molar mass of urea to solution B according to the pH value and the urea hydrolysis equation to adjust the pH of solution B to neutral; continuing to add a second molar mass of urea to the neutral solution B and stirring for 30 minutes to obtain the mixed solution, wherein the ratio of the second molar mass to the molar mass of nickel metal in the laterite nickel ore is 4:1; placing the initial foamed nickel material in the mixed solution, then placing the mixed solution into a 100 mL polytetrafluoroethylene (PTFE) high-pressure reactor, placing the PTFE high-pressure reactor in an oven for reaction at 160°C for 12 hours; after the reaction, removing the PTFE high-pressure reactor and cooling it to room temperature to obtain the composite material.

[0066] The composite material was cleaned with deionized water and ethanol, and then dried in a vacuum drying oven at 60°C for 12 hours to obtain scandium-doped nickel-iron-cobalt hydroxide.

[0067] 5-Hydroxymethylfurfural was dissolved in an alkaline solution to obtain solution C. Solution C, a reference electrode, a counter electrode, and the scandium-doped nickel-iron-cobalt hydroxide were placed in an H-type electrolytic cell. Solution C was then subjected to electrocatalytic conversion to obtain 2,5-furandicarboxylic acid. The concentration of 5-hydroxymethylfurfural was 10 mmol / L, the alkaline solution was a 1 mol / L KOH solution, the reference electrode was Hg / HgO, the counter electrode was a carbon rod, and the electrocatalytic conversion potential was 1.45 V (vs. RHE). Solution C was used as the electrolyte in the anolyte of the H-type electrolytic cell, and the electrolyte in the cathode of the H-type electrolytic cell was a 1 mol / L KOH solution without added 5-hydroxymethylfurfural.

[0068] Example 6

[0069] This embodiment prepares 2,5-furandicarboxylic acid from scandium-doped nickel-iron-cobalt hydroxide using the following steps:

[0070] Pretreatment of nickel foam material yields initial nickel foam material; the pretreatment of nickel foam material to obtain initial nickel foam material includes: cutting the nickel foam material with a thickness of 0.5 mm into a nickel foam sheet with a size of 1 cm × 1 cm × 0.5 mm, and subjecting the nickel foam sheet to ultrasonic treatment with hydrochloric acid for 15 min, ultrasonic treatment with acetone for 15 min, ultrasonic treatment with ethanol for 15 min, and ultrasonic treatment with ultrapure water for 15 min in sequence to obtain the initial nickel foam material, wherein the concentration of hydrochloric acid is 3 mol / L;

[0071] 600 mg of laterite nickel ore was placed in 80 mL of deionized water to form solution A. Concentrated sulfuric acid was added to solution A to adjust the pH to 1.2, and the mixture was stirred for 12 h to carry out the reaction. After the reaction was completed, solid-liquid separation was performed to obtain solution B.

[0072] Urea is added to solution B, and the mixture is stirred to obtain a mixed solution. The steps of adding urea to solution B and stirring to obtain the mixed solution include: detecting the pH value of solution B; adding a first molar mass of urea to solution B according to the pH value and the urea hydrolysis equation to adjust the pH of solution B to neutral; continuing to add a second molar mass of urea to the neutral solution B and stirring for 60 minutes to obtain the mixed solution, wherein the ratio of the second molar mass to the molar mass of nickel metal in the laterite nickel ore is 5:1; placing the initial foamed nickel material in the mixed solution, then placing the mixed solution into a 100 mL polytetrafluoroethylene (PTFE) high-pressure reactor, placing the PTFE high-pressure reactor in an oven for reaction at a reaction temperature of 200°C for 24 hours; after the reaction is completed, removing the PTFE high-pressure reactor and cooling it to room temperature to obtain the composite material.

[0073] The composite material was cleaned with deionized water and ethanol, and then dried in a vacuum drying oven at 60°C for 12 hours to obtain scandium-doped nickel-iron-cobalt hydroxide.

[0074] 5-Hydroxymethylfurfural was dissolved in an alkaline solution to obtain solution C. Solution C, a reference electrode, a counter electrode, and the scandium-doped nickel-iron-cobalt hydroxide were placed in an H-type electrolytic cell. Solution C was then subjected to electrocatalytic conversion to obtain 2,5-furandicarboxylic acid. The concentration of 5-hydroxymethylfurfural was 10 mmol / L, the alkaline solution was a 1 mol / L KOH solution, the reference electrode was Hg / HgO, the counter electrode was a carbon rod, and the electrocatalytic conversion potential was 1.55 V (vs. RHE). Solution C was used as the electrolyte in the anolyte of the H-type electrolytic cell, and the electrolyte in the cathode of the H-type electrolytic cell was a 1 mol / L KOH solution without added 5-hydroxymethylfurfural.

[0075] Example 7

[0076] This embodiment prepares 2,5-furandicarboxylic acid by scanning electron doping with nickel iron cobalt hydroxide according to the method of Example 5. The difference from Example 5 is that the concentration of 5-hydroxymethylfurfural is 100 mmol / L, and the remaining steps are the same as in Example 5.

[0077] Example 8

[0078] This embodiment prepares 2,5-furandicarboxylic acid from scandium-doped nickel-iron-cobalt hydroxide according to the method of Example 5. The difference from Example 5 is that the concentration of 5-hydroxymethylfurfural is 100 mmol / L, and the alkaline solution is a 3 mol / L KOH solution. The remaining steps are the same as in Example 5.

[0079] Experimental Results: The scandium-doped nickel-iron-cobalt hydroxide obtained in Example 5 was analyzed by electron microscopy (SEM) and X-ray diffraction (XRD). The analytical results are as follows: Figure 2 and Figure 3 As shown, the obtained substance is a scandium-doped nickel-iron-cobalt hydroxide catalyst with a self-assembled nanoflower-like structure. The 2,5-furandicarboxylic acid prepared in Examples 3-8 was analyzed by high-performance liquid chromatography (HPLC) to obtain its yield, and the Faradaic efficiency of the 2,5-furandicarboxylic acid prepared in Examples 3-8 was detected. The test results are shown in Table 2. It can be seen that the scandium-doped nickel-iron-cobalt hydroxide catalyst exhibits excellent electrocatalytic oxidation activity, and can directionally catalytically oxidize 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid under mild conditions with high conversion efficiency. Example 5 is the example under optimal conditions, and the yield and Faradaic efficiency of the 2,5-furandicarboxylic acid obtained through Example 5 are optimal.

[0080] Table 2

[0081] Example 3 81.8 80.6 Example 4 86.8 85.6 Example 5 93.9 91.2 Example 6 91.2 90.5 Example 7 92.3 91.1 Example 8 93.0 91.2

[0082] Finally, it should be noted that the terms “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0083] Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including both the preferred embodiments and all changes and modifications falling within the scope of the invention.

[0084] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. A method for preparing 2,5-furandicarboxylic acid from scandium-doped nickel-iron-cobalt hydroxide, characterized in that, The method includes: Pretreatment of nickel foam material yields initial nickel foam material; Lateritic nickel ore is placed in deionized water to form solution A. Concentrated sulfuric acid is added to solution A to adjust the pH and the mixture is stirred to carry out the reaction. The mass of the lateritic nickel ore is 200 mg to 600 mg, the volume of the deionized water is 30 mL to 80 mL, the pH value is 1.2 to 3.5, and the stirring time is 5 h to 12 h. After the reaction is completed, solid-liquid separation is performed to obtain solution B. Urea was added to solution B and stirred to obtain a mixed solution. The initial nickel foam material was placed in the mixed solution, and then the mixed solution was placed in a polytetrafluoroethylene high-pressure reactor. The polytetrafluoroethylene high-pressure reactor was placed in an oven for reaction at a temperature of 120°C to 200°C for a reaction time of 6 h to 24 h. After the reaction was completed, the polytetrafluoroethylene high-pressure reactor was removed and cooled to room temperature to obtain the composite material. The composite material was cleaned with deionized water and ethanol, and then dried in a vacuum drying oven to obtain scandium-doped nickel-iron-cobalt hydroxide, which is a self-assembled nanoflower-like structure. 5-Hydroxymethylfurfural was dissolved in an alkaline solution to obtain solution C. Solution C, a reference electrode, a counter electrode, and the scandium-doped nickel-iron-cobalt hydroxide were placed in an H-type electrolytic cell. Then, solution C was subjected to electrocatalytic conversion to obtain 2,5-furandicarboxylic acid. The step of adding urea to solution B and stirring to obtain a mixed solution includes: The pH value of solution B is measured; According to the pH value and the urea hydrolysis equation, a first mole mass of urea is added to solution B to adjust the pH of solution B to neutral. Add a second molar mass of urea to the neutral solution B and stir for 10 min to 60 min to obtain the mixed solution. The ratio of the second molar mass to the molar mass of nickel metal in the laterite nickel ore is 2:1 to 5:

1.

2. The method for preparing 2,5-furandicarboxylic acid from scandium-doped nickel-iron-cobalt hydroxide according to claim 1, characterized in that, The pretreatment of the nickel foam material to obtain the initial nickel foam material includes: The 0.5 mm thick nickel foam material was cut into nickel foam sheets with dimensions of 1 cm × 1 cm × 0.5 mm. The nickel foam sheets were then subjected to ultrasonic treatment with hydrochloric acid for 15 min, ultrasonic treatment with acetone for 15 min, ultrasonic treatment with ethanol for 15 min, and ultrasonic treatment with ultrapure water for 15 min in sequence to obtain the initial nickel foam material. The concentration of the hydrochloric acid was 3 mol / L.

3. The method for preparing 2,5-furandicarboxylic acid from scandium-doped nickel-iron-cobalt hydroxide according to claim 2, characterized in that: The polytetrafluoroethylene high-pressure reactor is placed in an oven for the reaction, and the capacity of the polytetrafluoroethylene high-pressure reactor is 100 mL. The cleaned composite material is placed in a vacuum drying oven for drying at a temperature of 60 °C for 12 h.

4. The method for preparing 2,5-furandicarboxylic acid from scandium-doped nickel-iron-cobalt hydroxide according to claim 3, characterized in that: The concentration of 5-hydroxymethylfurfural is 10 mmol / L to 100 mmol / L, the alkaline solution is 1 mol / L to 3 mol / L KOH solution, the reference electrode is Hg / HgO, the counter electrode is a carbon rod, and the electrocatalytic conversion potential is 1.4 V to 1.6 V vs. RHE.

5. A method for preparing scandium-doped nickel-iron-cobalt hydroxide derived from laterite nickel ore, characterized in that, The preparation method includes: Pretreatment of nickel foam material yields initial nickel foam material; Lateritic nickel ore is placed in deionized water to form solution A. Concentrated sulfuric acid is added to solution A to adjust the pH and the mixture is stirred to carry out the reaction. The mass of the lateritic nickel ore is 200 mg to 600 mg, the volume of the deionized water is 30 mL to 80 mL, the pH value is 1.2 to 3.5, and the stirring time is 5 h to 12 h. After the reaction is completed, solid-liquid separation is performed to obtain solution B. Urea was added to solution B and stirred to obtain a mixed solution. The initial nickel foam material was placed in the mixed solution, and then the mixed solution was placed in a polytetrafluoroethylene high-pressure reactor. The polytetrafluoroethylene high-pressure reactor was placed in an oven for reaction at a temperature of 120°C to 200°C for a reaction time of 6 h to 24 h. After the reaction was completed, the polytetrafluoroethylene high-pressure reactor was removed and cooled to room temperature to obtain the composite material. The composite material was cleaned with deionized water and ethanol, and then dried in a vacuum drying oven to obtain scandium-doped nickel-iron-cobalt hydroxide, which is a self-assembled nanoflower-like structure. The step of adding urea to solution B and stirring to obtain a mixed solution includes: The pH value of solution B is measured; According to the pH value and the urea hydrolysis equation, a first mole mass of urea is added to solution B to adjust the pH of solution B to neutral. Add a second molar mass of urea to the neutral solution B and stir for 10 min to 60 min to obtain the mixed solution. The ratio of the second molar mass to the molar mass of nickel metal in the laterite nickel ore is 2:1 to 5:

1.

6. The method for preparing scandium-doped nickel-iron-cobalt hydroxide derived from laterite nickel ore according to claim 5, characterized in that, The pretreatment of the nickel foam material to obtain the initial nickel foam material includes: The 0.5 mm thick nickel foam material was cut into nickel foam sheets with dimensions of 1 cm × 1 cm × 0.5 mm. The nickel foam sheets were then subjected to ultrasonic treatment with hydrochloric acid for 15 min, ultrasonic treatment with acetone for 15 min, ultrasonic treatment with ethanol for 15 min, and ultrasonic treatment with ultrapure water for 15 min in sequence to obtain the initial nickel foam material. The concentration of the hydrochloric acid was 3 mol / L.

7. The method for preparing scandium-doped nickel-iron-cobalt hydroxide derived from laterite nickel ore according to claim 6, characterized in that: The polytetrafluoroethylene high-pressure reactor is placed in an oven for the reaction, and the capacity of the polytetrafluoroethylene high-pressure reactor is 100 mL. The cleaned composite material is placed in a vacuum drying oven for drying at a temperature of 60 °C for 12 h.

8. A scandium-doped nickel-iron-cobalt hydroxide derived from laterite nickel ore, characterized in that, The scandium-doped nickel-iron-cobalt hydroxide, prepared by the method according to any one of claims 5-7, has the following uses: It is used as an electrocatalyst in the preparation of 2,5-furandicarboxylic acid.

Citation Information

Patent Citations

  • Preparation method and application of catalyst based on laterite-nickel ore

    CN117286529A